1989
DOI: 10.1172/jci114322
|View full text |Cite
|
Sign up to set email alerts
|

Tumor vascular permeability factor stimulates endothelial cell growth and angiogenesis.

Abstract: Vascular permeability factor (VPF) is an Mr 40-kD protein that has been purified from the conditioned medium of guinea pig line 10 tumor cells grown in vitro, and increases fluid permeability from blood vessels when injected intradermally. Addition of VPF to cultures of vascular endothelial cells in vitro unexpectedly stimulated cellular proliferation. VPF promoted the growth of new blood vessels when administered into healing rabbit bone grafts or rat corneas. The identity of the growth factor activity with V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
612
3
28

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,179 publications
(660 citation statements)
references
References 25 publications
17
612
3
28
Order By: Relevance
“…These functions are essential steps for neovessel sprouting (Kubota et al, 1988;Connolly et al, 1989) and angiogenesis, which is an important biological process involved in metastasis formation (Liotta et al, 1991;Weidner et al, 1991). Importantly, throughout the experiment with the CAM model, this study showed NAMI-A to prevent in vivo angiogenesis at doses known to have anti-metastasis activity.…”
Section: Discussionmentioning
confidence: 64%
“…These functions are essential steps for neovessel sprouting (Kubota et al, 1988;Connolly et al, 1989) and angiogenesis, which is an important biological process involved in metastasis formation (Liotta et al, 1991;Weidner et al, 1991). Importantly, throughout the experiment with the CAM model, this study showed NAMI-A to prevent in vivo angiogenesis at doses known to have anti-metastasis activity.…”
Section: Discussionmentioning
confidence: 64%
“…Many fundamental processes, mediators and regulators of airways disease pathogenesis were discovered or demonstrated first in guinea pigs, including the Schultz-Dale (immediate type hypersensitivity) reaction, the actions of histamine, the cysteinyl-leukotrienes and their two receptors, beta adrenoceptor subtypes, thromboxane, vascular endothelial growth factor (VEGF), eotaxin, alveolar macrophage derived neutrophil chemotactic factor(s) (leukotriene B 4 and/or IL-8) and the roles of cAMP and inositol triphosphate in signal transduction [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Receptor pharmacology in guinea pigs more closely matches that of human receptor pharmacology than most other commonly used species [1,20,21] (Table 1, Figs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that Vascular Endothelial Growth Factor (VEGF), also referred to as Vascular Permeability Factor (VPF), is an important element for many angiogenic processes under normal and abnormal states Shibuya, 1995;Mustonen and Alitro, 1995). VEGF carries two major biological activities, one is the capacity to stimulate vascular endothelial cell proliferation (Ferrara and Henzel, 1989;Leung et al, 1989;Connolly et al, 1989) and the other is the ability to increase microvessel permeability to macromolecules (Senger et al, 1983;Keck et al, 1989). In addition, some additional biological activities have recently been reported: VEGF was found to stimulate macrophage migration (Clauss et al, 1993;Barleon et al, 1996), protease production in endothelial cells (Pepper et al, 1991;Unemori et al, 1992) and the resistance of hematopoietic cells to radiation-induced apoptosis (Katoh et al, 1995).…”
Section: Introductionmentioning
confidence: 99%